Adenoid hypertrophy in children: a narrative review of pathogenesis and clinical relevance - Artur Niedzielski; Lechosław Paweł Chmielik; Grażyna Mielnik-Niedzielska; Anna Kasprzyk; Joanna Bogusławska (BMJ Publishing Group, 2023)
Adenoids (nasopharyngeal tonsils), being part of Waldeyer's ring, are masses of lymphoid tissues located at the junction of the roof and the posterior wall of the nasopharynx. Adenoids play an important role in the development of the immune system and serve as a defence against infections, being the first organs that come into contact with respiratory and digestive antigens. The causes of adenoid hypertrophy are not fully known. They are most likely associated with aberrant immune reactions, infections, environmental exposures and hormonal or genetic factors. The aim of this review is to summarise the current knowledge of adenoid hypertrophy in children and associated diseases. Adenoid hypertrophy has many clinical manifestations that are frequent in the paediatric population and is accompanied by various comorbidities.